СУЧАСНІ МОДЕЛІ ТРАНСФЕРУ ТЕХНОЛОГІЙ У СИСТЕМІ «УНІВЕРСИТЕТ – ВЛАДА – БІЗНЕС» (International Journal of Innovative Technologies in Economy, 2018)
The development of the concept of open innovations has led to the revision of the approaches to technology transfer by the countries of the world: the key role in this process is assigned to universities. Currently, in Ukraine, there is no unity in the interaction between universities and businesses. This indicates the need to reformat the approaches to the implementation of technology transfer in Ukrainian universities. For this purpose, a conceptual model of technology transfer through the establishment of businesses was justified in this article. Unlike the existing model of technology transfer, the model of changing the roles offered in the article Model of Technology Transfer through the Establishment of Businesses describes technology transfer that corresponds to the model of triple helix of University – Authority – Business interaction based on the modern function of technology and on the relationship between the Technology Push / Market Pull, and involves a systematic approach to technology transfer from universities to the business environment.